THE PERSONAL LENS IN ACADEMIC EVALUATION: A CRITIQUE OF EDUCATOR BIAS - Siddiqui, Hassan Rasheed (The journal of contemporary issues in business and government, 2013)
Employing a case study, this paper takes a critical perspective toward concerns over plagiarism policies in institutions of higher education, demonstrating how these policies are potentially subject to misinterpretation, disproportionate enforcement, and administrative inefficacy. In the investigated case, a student was suspected of having plagiarized work for a corporate governance course, which was punishable by academic sanctions based on vague institutional guidelines, leaving room for subjective interpretation by faculty. The paper identifies four central issues: 1) the guidelines for plagiarism lack precision, which promotes heterogeneous policing of the rules; 2) procedural fairness is absent in the management of the cases, as personal prejudices affect judgments; 3) responsibility and definition of the boundaries of institutional bodies has broken down and induces a great delay and confusion; and 4) students undergoing investigations are left with psychological and emotional damages. The case highlights the urgent need for clarity, consistency and transparency in plagiarism policies, independent review processes, and improved communications pathways between departs and support systems for students accused of plagiarism. “Plagiarism policies must be rational, proportional and, above all, fair,” said the study, calling for “an urgent need for overhaul” of how academic institutions punish students over plagiarism. In conclusion, the paper highlights the need for promoting a fair and transparent academic environment that upholds academic integrity while also considering the well-being, and professional growth of students.